In search of the shortest regimen: fractionation of a fully isoeffective combination of hyperfractionated and hypofractionated treatment - Strojnik, Andrej (Radiology and oncology (Ljubljana), 2008)
Purpose. To analyze the possibility of reducing the number of fractions but maintaining the full biological effect of radiotherapy by varying the dose perfraction. Methods. An arbitrary treatment with a constant dose per fractionis substituted for a fully isoeffective combination of a hyperfractionated and hypofractionated treatment. The number of fractions of the combined treatment is derived. All calculations are based on the linear-quadratic model. Conclusions. Standard uniform fractionation requires the fewest fractions. Any variation in dose per fraction increases the number of fractions of a fully isoeffective treatment.
Keywords: onkologija; radioterapija; Radioterapija, doziranje; Radiotherapy Dosage; therapy; zdravljenje